Identifying cellular pathways modulated by Drosophila palmitoyl-protein thioesterase 1 function. - Saja, S.; Buff, H.; Smith, A.C.; Williams, T.S.; Korey, C.A. (Neurobiology of Disease, 2010)
Infantile-onset Neuronal Ceroid Lipofuscinosis (INCL) is a severe pediatric neurodegenerative disorder produced by mutations in the gene encoding palmitoyl-protein thioesterase 1 (Ppt1). This enzyme is responsible for the removal of a palmitate post-translational modification from an unknown set of substrate proteins. To better understand the function of Ppt1 in neurons, we performed an unbiased dominant loss-of-function genetic modifier screen in Drosophila using a previously characterized Ppt1 gain-of-function system. The enhancers and suppressors identified in our screen make novel connections between Ppt1 and genes involved in cellular trafficking and the modulation of synaptic growth. We further support the relevance of our screen by demonstrating that Garland cells from Ppt1 loss-of-function mutants have defects in endocytic trafficking. Endocytic tracer uptake and ultrastructural analysis of these non-neuronal cells points to Ppt1 playing a role in modulating the early stages of vesicle formation. This work lays the groundwork for further experimental exploration of these processes to better understand their contributions to the INCL disease process.